Education and Training on Making Carrot Hard Candy and Dragon Fruit Soft Candy for Stunting Prevention - Raising, Rahmawati; Hermawatiningsih, Oktaviarika Dewi; Rumaolat, Wiwi; Pelu, Aulia Debby (Jurnal IPMAS, 2024)
Stunting is a form of chronic malnutrition associated with prolonged nutritional deficiencies. One crucial way to meet the nutritional needs of young children is by consuming vegetables and fruits, which are primary sources of micronutrients. Vegetables and fruits are vital for the body as sources of vitamins, minerals, and fiber, essential for achieving a healthy diet according to balanced nutrition guidelines. Vitamins are particularly crucial for maintaining body health. Carrots (Daucus carota L) and dragon fruit (Hylocereus sp.) are highly nutritious vegetables and fruits, containing high levels of carotene, vitamin A, B, C, and various minerals. Providing education and training to individuals and community groups, especially those at risk, aims to enhance knowledge, foster healthy habits and behaviors, and ultimately prevent stunting in the community. This community service project consists of preparation, observation, and implementation stages. The project involved 30 participants from the community and the PKK women's group in Kerang Village, Takeran District, Magetan Regency, East Java Province. The results indicated high participant enthusiasm, as seen from their active engagement. The community learned about the benefits of carrot hard candy and dragon fruit soft candy and understood the process of making these nutritious candies. From a low level of understanding before the education, there was an increase in understanding, and the community's low skill level improved after the training.